2019
DOI: 10.1007/s12282-019-00980-5
|View full text |Cite
|
Sign up to set email alerts
|

Icariin induces apoptosis by suppressing autophagy in tamoxifen-resistant breast cancer cell line MCF-7/TAM

Abstract: Background Icariin is a major component isolated from Epimedium brevicornum Maxim and has been reported to exhibit anti-tumor activity. However, whether icariin could reverse the acquired drug resistance in breast cancer remains largely unclear. Therefore, this study was designed to explore the antitumor effects of icariin and its underlying mechanisms in a tamoxifen-resistant breast cancer cell line MCF-7/TAM. Methods 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and Lactate dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Resveratrol improves the sensitivity of BC chemotherapy and prevents the development of cancer by targeting miR-122-5, and then influences the expression of CDK2, CDK4, and CDK6, resulting in cell-cycle arrest [162]. Icariin, the main component with antitumor activity extracted from Epimedium brevicornum Maxim, decreases the expression of CDK2 and CDK4 to cause cell-cycle arrest in tamoxifen-resistant BC cell line MCF-7/TAM [163]. Tyrosine kinase WEE1 inhibitor AZD 1775 shows strong anti-proliferative effects.…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…Resveratrol improves the sensitivity of BC chemotherapy and prevents the development of cancer by targeting miR-122-5, and then influences the expression of CDK2, CDK4, and CDK6, resulting in cell-cycle arrest [162]. Icariin, the main component with antitumor activity extracted from Epimedium brevicornum Maxim, decreases the expression of CDK2 and CDK4 to cause cell-cycle arrest in tamoxifen-resistant BC cell line MCF-7/TAM [163]. Tyrosine kinase WEE1 inhibitor AZD 1775 shows strong anti-proliferative effects.…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…Beclin 1 has been identified as a mammalian protein associated with autophagy and involved in cancer processes such as tumor suppression and cell death (48). Cheng et al (49) identified the role of autophagy in MCF-7 cells treated with Icariin (a flavonoid isolated from plants) by measuring the expression levels of ATG5, Beclin 1 and LC3-I to LC3-II proteins. Liang et al (50) demonstrated that exogenous Beclin 1 expression in MCF-7 cells resulted in decreased cell division and inhibition of tumorigenesis in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have found that treatment of T-cell malignancies is accompanied with autophagy regulation 21 24 . Emerging reports have indicated that some flavonoids promote cell death by mediating autophagy in tumor cells 25 27 , such as wogonin 28 30 . FV-429, a derivative of wogonin, has been proved to exert anti-cancer effects in several solid tumors 31 33 .…”
Section: Introductionmentioning
confidence: 99%